Production of particle board from banana leaves - Wan Suhardi Wan Md. Sukri (Universiti Malaysia Perlis, 2009)
The method of agricultural waste disposal involving open burning which often to be used by the banana plantations entrepreneur is unpractical where it is contribute to air pollution. Base on the situation above, this study is tried to reduce air pollution and wasted raw material beside to increase the income of farmer by producing particle board from banana leaves. This study produced by mixing banana leaves with urea formaldehyde (UF) resin then pressed through a hot compression machine to form the particle board. Several testing methods were used to characterize the particle board such as flexural test, Fourier Transform Infra-Red (FTIR) spectroscopy, Thermogravimetric Analysis (TGA), water absorption and thickness swelling. The parameters determined the effect of UF resin ratio that were mixed with the banana leaves as hardener on physical properties of the particle board such as flexural strength, water absorption and thickness swelling. The result was compared with conventional particle board. From the flexural test the highest flexural strength was at highest weight percentage of UF resin. Low operation cost and availability of cheap raw material make this banana leaves can be commercialized as new material for particle board. However the study of variation parameter such as effect of temperature reaction, time reaction and effect of various adhesive types must be carry out.